Trans Young Adults’ Building Communities: Narratives and Counternarratives of Identity and World Making: Michelle Lavoie (LEARNing Landscapes, 2022)
This paper draws on a three-year inquiry, in which I lived alongside three trans young adults amid their unfolding lives. I used narrative inquiry, a relational methodology that holds relationship central, to explore asset-building processes within relational learning. This article showcases participants’ use of artworks, stories, and counterstories to understand experiences and engage communities. Additionally, this study highlights how trans young adults transform their identities at the intersections of race, citizenship, ableism, and health. This research demonstrates the complexity of trans: identity formation; intersectional tensions, and creative possibilities; and, performativity of intersectionality and identities across multiple communities’ spaces and places.
Keywords: counternarratives; counternarrative; visual narrative inquiry; narrative inquiry; trans; trans gender; community building